Dramatic response to neoadjuvant savolitinib in marginally resectable lung adenocarcinoma with MET exon 14 skipping mutation: A case report and literature review - Tian, Jiangfang; Lin, Zhen; Chen, Yueyun; Fu, Yang; Ding, Zhenyu (Frontiers in Oncology, 2022)
Mesenchymal–epithelial transition (MET) exon 14 skipping mutation (METex14) is a low-frequency driver mutation in metastatic non-small cell lung cancer (NSCLC) (3%–4%) and is associated with a poor prognosis. With the advent of selective MET inhibitors such as capmatinib, tepotinib, and savolitinib, the outcome for these patients was significantly improved. Here, we report a 76-year-old male patient with marginally resectable stage IIIB lung adenocarcinoma harboring METex14 who was successfully treated with savolitinib for neoadjuvant therapy. An 82% shrinkage of the primary tumor was observed, and only 5% of the tumor was viable by pathology in the following radical surgery. A dozen of studies tested the efficiency of neoadjuvant immunotherapy or immunochemotherapy, but for NSCLC with driver mutations, neoadjuvant targeted therapy might be more appropriate. We advocated the neoadjuvant MET TKI treatment for NSCLC.